The importance of etching in spreading the grotesque depiction of demons by Ars Moriendi in our imagination - Silva, Wilson Roberto da (Revista do Colóquio, 2025)
This article focuses on Ars Moriendi and how it relates to the aesthetic category of the grotesque, despite the doctrinal component embedded in its visual messages. It highlights the importance of etching in disseminating the imagery surrounding the Last Judgment, hell, and the demons that inhabit it, as something provocative that destabilizes and repulses like any grotesque image. Etching was responsible for spreading this imagery, and although subordinate among the means considered artistic, it became suitable for disseminating this imagery that inhabits us to this day.